Business development : a guide to small business strategy - Butler, David, 1951- (Oxford ; Boston ; Butterworth-Heinemann, 2001)
Shows how to make the most of the stages of growth most businesses pass through at some point. It shows how to deal with the different types of problems that are encountered during this process.
Includes bibliographical references and index.
oif 23/03/15
Loan
Keywords: Small business -- Growth; Strategic planning